In Memory of Petro M. Tsarenko (12.07.1956 – 21.01.2023) (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2023)
A brief biography and obituary, in memory of Petro M. Tsarenko (1956-2023), a prominent Ukrainian phycologist.